2022
DOI: 10.1103/physrevlett.129.128002
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Control of Activity Patterns in Cytoskeletal Networks

Abstract: Biological materials, such as the actin cytoskeleton, exhibit remarkable structural adaptability to various external stimuli by consuming different amounts of energy. In this Letter, we use methods from large deviation theory to identify a thermodynamic control principle for structural transitions in a model cytoskeletal network. Specifically, we demonstrate that biasing the dynamics with respect to the work done by nonequilibrium components effectively renormalizes the interaction strength between such compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Such extensile flows have been reported for both microtubule/kinesin [14] and actomyosin [29,30] based materials. Theoretical work has suggested that extensile stresses could arise from the polarity sorting of filaments [31] or the mechanical properties of the motors themselves [32,33]. Under other conditions, both microtubule and actin-based active gels have been found to undergo bulk contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Such extensile flows have been reported for both microtubule/kinesin [14] and actomyosin [29,30] based materials. Theoretical work has suggested that extensile stresses could arise from the polarity sorting of filaments [31] or the mechanical properties of the motors themselves [32,33]. Under other conditions, both microtubule and actin-based active gels have been found to undergo bulk contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Similar DPTs have been described through the application of LDT to the distribution of entropy production in systems such as active Brownian particles, with a phase transition marked by a collective particle alignment [86]. Furthermore, LDT may aid in uncovering DPTs in other systems, such as chemical reaction networks or conformational changes in energy-driven biomolecules, by identifying rare dynamical regimes of their dynamics [225]. At larger scales, in the area of climatology and geophysical modeling, LDT has gained prominence in evaluating climate anomalies, including sustained, long-term heat waves across spatially extended regions (see Fig.…”
Section: Introduction: Why Large Deviations?mentioning
confidence: 78%
“…Yet, these models pre-suppose a particular migration mechanism, and the mechanism for upstream choice of which mode to choose from is left open. Though far removed from the complexity of a whole cell, some inspiration might come from thermodynamic control theory applied to networks of out-of-equilibrium filaments, such as the cytoskeleton Lamtyugina et al (2021). Based on this work, it has been suggested that energy resources and external cues could effectively modify cytoskeletal material properties and drive transitions between many-filament structures Lamtyugina et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Though far removed from the complexity of a whole cell, some inspiration might come from thermodynamic control theory applied to networks of out-of-equilibrium filaments, such as the cytoskeleton Lamtyugina et al (2021). Based on this work, it has been suggested that energy resources and external cues could effectively modify cytoskeletal material properties and drive transitions between many-filament structures Lamtyugina et al (2021). It will be interesting to apply this approach to active droplets in which different migration modes can be associated with dynamic structural transitions of the material.…”
Section: Discussionmentioning
confidence: 99%